1997
DOI: 10.1161/01.cir.96.10.3542
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Complement System During and After Cardiopulmonary Bypass Surgery

Abstract: Cardiac surgery with CPB causes a biphasic complement activation. The first phase occurs during CPB and results from the interaction of blood with the extracorporeal circuit. The second phase, which occurs during the first 5 days after surgery, involves CRP, is related to baseline CRP levels, and is associated with clinical symptoms such as arrhythmia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
214
1
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 676 publications
(230 citation statements)
references
References 28 publications
7
214
1
8
Order By: Relevance
“…Preoperative CRP levels were similar in both groups, which is a finding consistent with the results of Bruins et al 14 Aviles and colleagues 3 have demonstrated the association between CRP and AF only in patients with persistent or chronic AF, not in patients with a single episode of short-term AF after surgery.…”
Section: Mandal Et Al Hsp60 Antibodies and Atrial Fibrillation 2589supporting
confidence: 88%
“…Preoperative CRP levels were similar in both groups, which is a finding consistent with the results of Bruins et al 14 Aviles and colleagues 3 have demonstrated the association between CRP and AF only in patients with persistent or chronic AF, not in patients with a single episode of short-term AF after surgery.…”
Section: Mandal Et Al Hsp60 Antibodies and Atrial Fibrillation 2589supporting
confidence: 88%
“…The inflammatory process after CPB has its final lesion characterized by an increase of diffuse capillary permeability with significant liquid extravasation towards the interstitial tissue [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] . This finding could be partially explained by the presence of what is currently called endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, there is a stimulation of leukocytes, monocytes, macrophages, basophils, endothelial cells, myocytes and hepatocytes. There is an increase in the circulation of complement fractions (mainly C3a, C4a and C5a) 5,6 , citokynes (mainly tumor necrosis factoralpha, class 1, 6, 8 and 10 interleukins) [7][8][9] , histamine 10 and adhesion molecules 11. The inflammatory cascade is then amplified and may be associated with clinical manifestations by fever occurrences 12,13 , myocardial dysfunction (due to mechanical, ischemic and immunological injury) 14,15 and/or vasoplegy 16,17 , with occurrence of hypotension; signs of low cardiac output with hyperperfusion and tissular hypoxia; acute renal insufficiency 18,19 ; acute pulmonary lesion 20 , acute respiratory distress syndrome 21 ; blood dyscrasia 22 , neurological symptoms 23,24 and liquid retention with weight gain down to endothelial lesion 25 . When present, these manifestations may prolong the period of stay in ICU and in general hospital due to aggregated morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…There is persistence of CRP, IL6, and TNF-a (tumor-necrosis factor-a) in paroxysmal AF long after successful cardioversion, perhaps indicating a causative role (Aviles et al, 2003). Increases of IL6, CRP, and the white blood cell count correlate with onset of AF after cardiac surgery (Bruins et al, 1997). Urgently admitted AF patients often have pneumonia (Lip et al, 1995).…”
Section: Insights Into Molecular Mechanisms Of Cardioembolic Ischemicmentioning
confidence: 99%